Daily health concerns in Kakabo anthropological explorations in a Bangladeshi village - Geest, Sjaak Van der; Selim, Nasima; Zaman, Shahaduz (James P. Grant School of Public Health, BRAC University, 2010)
Includes bibliographical references (pages 135 - 145).